New to New York: Ecological and Psychological Predictors of Health Among Recently Arrived Young Adult Gay and Bisexual Urban Migrants. - Pachankis, John E; Eldahan, Adam I; Golub, Sarit A (Annals of behavioral medicine : a publication of the Society of Behavioral Medicine, 2016)
Young gay and bisexual men might move to urban enclaves to escape homophobic environments and achieve greater sexual and social freedom, yet little is known about the health risks that these young migrants face.